Traumatic primary enterocutaneous fistula: a case report - Aher, Kalyani D.; Gadahire, Minakshi (International Journal of Research in Medical Sciences, 2026)
Enterocutaneous fistula (ECF) is an abnormal communication between the gastrointestinal tract and the skin. Approximately 80% of ECFs occur as a complication of surgical procedures, while the remaining 20% are associated with trauma, inflammatory bowel disease (such as Crohn’s disease), radiation exposure, or malignancy. In trauma patients without prior abdominal surgery, primary traumatic enterocutaneous fistulas (ECFs) are rare, accounting for less than 1.5% to 5% of all ECF cases. We present a case of a 14-year-old male who developed an enterocutaneous fistula following abdominal trauma caused by a bicycle handle injury. The patient presented with feculent discharge seven days after the incident. Notably, the site of trauma was located on the anterior abdominal wall, whereas the fistula opening was identified posteriorly, corresponding to the exact counterpoint of the injury. The patient had no prior history of any surgical intervention.